2012
DOI: 10.1007/s10856-012-4583-9
|View full text |Cite
|
Sign up to set email alerts
|

Autologous urothelial cells transplantation onto a prefabricated capsular stent for tissue engineered ureteral reconstruction

Abstract: In this study, we have fabricated an artificial ureter by transplantation of in vitro-expanded urothelial cells onto an in vivo-prefabricated capsular stent using tissue engineering methods. Spiral poly (L-lactic acid) (PLLA) stents were transplanted into the subcutaneous of Wistar rats for a period of 1, 2 or 3 weeks to induce the formation of connective tissue capsules on their surfaces. The capsular PLLA stents were then decellularized and further recellularized with bladder epithelial cells to fabricate ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…This way the initial tissue contraction takes place in a more controlled environment, without the toxic influences of urine (Adamowicz et al , ). Recent studies have shown the successful application of these techniques by implanting the tissue in non‐functional locations (Fu et al , ; Shi et al , ; Xu et al , ), as well as using them for ureteral repair afterwards (Liao et al , ; Zhang et al , ). Pre‐implantation before functional implantation may therefore improve the outcome of the reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…This way the initial tissue contraction takes place in a more controlled environment, without the toxic influences of urine (Adamowicz et al , ). Recent studies have shown the successful application of these techniques by implanting the tissue in non‐functional locations (Fu et al , ; Shi et al , ; Xu et al , ), as well as using them for ureteral repair afterwards (Liao et al , ; Zhang et al , ). Pre‐implantation before functional implantation may therefore improve the outcome of the reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…At nine weeks of development, the metanephros, which will become the mature kidney, starts to produce urine (21). Knowledge of the structure of the ureter in anencephalic fetuses is of great importance, since there are reports of an anencephalic fetus transplant donor with chronic renal failure where the ureter was used to divert urine (22). Such engineered tissue can be useful in the future for ureteral reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in three recent studies, the authors refrained from implantation of tissue-engineered constructs in an induced ureteral defect model. Instead, the authors performed subcutaneous implantations in rats (Xu, et al [ 26 ]) and mice (Shi, et al [ 27 ] and Fu, et al [ 28 ]). While these studies showed the potential of pre-implantation for ureteral replacement, information about the behavior of the construct as ureteral replacement is lacking.…”
Section: Ureteral Defect Repairmentioning
confidence: 99%
“…All three studies used a similar spiral poly( l -lactic acid) (PLLA) stent as the backbone of their construct. Xu et al [ 26 ] implanted the spiral PLLA stents in the subcutis and used the body as a natural bioreactor to generate a tissue fleece around the stent. The newly formed tissue was then decellularized and re-seeded with primary urinary bladder urothelial cells.…”
Section: Ureteral Defect Repairmentioning
confidence: 99%
See 1 more Smart Citation